Геоінформаційні моделі рельєфу річкових долин Дністровського каньйону - Триснюк, В.М. (Екологічна безпека та природокористування, 2012)
The proposed GISD niesterbasin with Bank environmental and economic and inventory information to support decision-making authorities. International experience has shown that the best way to represent, store and process information that has a spatial component (geo-referenced), is a geographic information system (GIS).